Technical feasibility of the incorporation of rice husk ash, sludge from water treatment plant and wood ash in clay for ceramic coating - Elisandra Nazaré Maia de Medeiros (Rem: Revista Escola de Minas, 2014)
This paper presents a technical feasibility analysis of the incorporation of Rice Husk Ash (RHA), Sludge from Water Treatment Station (SWTS) and Wood Ash (WA) in clay for the mass used in ceramic coating. The methodology in - volved analyzing the technological properties of various compositions. Samples were prepared for pressing, with compositions from 0 to 50% waste and 50 to 100% clay. The sintering was carried out in a muffle furnace. The properties studied were: solubility and leaching (environmental characterization), water ab - sorption and rupture strength modulus. It was concluded that the best condition was the use of up to 25% of the residuals at temperatures of 1000 °C, 1100 °C and 1150 °C.